An investigation into the effects of ex vivo antioxidant treatment on the regenerative potential of mesenchymal stem cells following prolonged exposure to a pathological microenvironment associated with diabetes mellitus in vivo - Mehrbani Azar, Yashar (Stellenbosch -- Stellenbosch University., 2019)
Thesis (PhD)--Stellenbosch University, 2019.